2006
DOI: 10.1097/01.mpg.0000228125.70971.af
|View full text |Cite
|
Sign up to set email alerts
|

Oligosaccharides in Colostrum of Italian and Burkinabe Women

Abstract: Human milk contains a large number of compounds to provide nutrition and defense for the newborn. Among these, oligosaccharides are present in concentrations up to 12 g/L, and their composition varies during lactation. Colostrum from 53 Burkinabe women were collected at the maternity department of St Camille Medical Centre in Ouagadougou (Burkina Faso, West Africa). Colostrum from 50 Italian women were collected at the maternity department of St Bambino Hospital in Catania (Catania, East Sicily, Italy). All mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 29 publications
4
46
1
Order By: Relevance
“…Characterization of HMO has been accomplished using HPAEC and HPLC in combination with derivatization techniques [4,[21][22][23][24]. The identification of HMOs was based on the retention time of commercially available milk oligosaccharide standards and their quantification was relative to the amount of standards.…”
Section: Milk Oligosaccharidesmentioning
confidence: 99%
“…Characterization of HMO has been accomplished using HPAEC and HPLC in combination with derivatization techniques [4,[21][22][23][24]. The identification of HMOs was based on the retention time of commercially available milk oligosaccharide standards and their quantification was relative to the amount of standards.…”
Section: Milk Oligosaccharidesmentioning
confidence: 99%
“…Several methods for the separation and quantification of neutral compounds in human milk have been described, including high-performance liquid chromatography (HPLC) [12][13][14][15] and capillary electrophoresis (CE) of derivatized HMOS [16], and HPLC with high pH amperometric detection of underivatized HMOS [17]. Acidic oligosaccharides have been resolved by anion exchange HPLC of radiolabelled derivatives [18], derivatization of the oligosaccharides followed by ion exchange LC with absorption at 200 nm [19] and capillary electrophoresis of fluorescent derivatives [20,21].…”
Section: Introductory Statementmentioning
confidence: 99%
“…The applicant indicated that the content of 2'-FL in colostrum ranged from 1 120 to 4 900 mg/L (Musumeci et al, 2006;Bao et al, 2013); however, concentrations of 8 400 mg/L have also been reported from secretor phenotype mothers (Musumeci et al, 2006).…”
Section: Safety Of 2'-o-fucosyllactosementioning
confidence: 99%
“…The applicant provided several publications on the 2'-FL content in human milk in relation to secretorand Lewis-blood group status (Thurl et al, 1997;Galeotti et al, 2012Galeotti et al, , 2014, ethnicity (Erney et al, 2000;Musumeci et al, 2006), lactation period (Coppa et al, 1999;Erney et al, 2000;Sumiyoshi et al, 2003;Asakuma et al, 2008;Leo et al, 2010;Bao et al, 2013), preterm birth (Nakhla et al, 1999;Gabrielli et al, 2011), and in mature milk (Chaturvedi et al, 1997(Chaturvedi et al, , 2001aErney et al, 2000Erney et al, , 2001Sumiyoshi et al, 2003;Morrow et al, 2004;Leo et al, 2010;Thurl et al, 2010;Asakuma et al, 2011;Coppa et al, 2011;Galeotti et al, 2012;Smilowitz et al, 2013;Hong et al, 2014). The concentration of 2'-FL in breast milk appears to depend on the lactation period, with higher levels reported in colostrum and decreased levels observed thereafter (Erney et al, 2000).…”
Section: Safety Of 2'-o-fucosyllactosementioning
confidence: 99%
See 1 more Smart Citation